Some Notes on Past and Future of the (Practice) PhD - Thea Brejzek; Lawrence Wallen (Cubic Journal)
This article traces the history of the PhD, the rise of the practice PhD and our experiences with implementing a practice-informed PhD programme between Vienna and Zurich, and it concludes with a reflection on some precarious parallels between the research , the methodology of a practice PhD and the decolonisation of research. Accompanying the article are images of our master’s and PhD candidates engaging globally in field research, archive research, creative practice and institutional and noninstitutional collaborations.